Design a Sign Language Translator Using Flexible Sensors - Iis Hamsir Ayub Wahab; Zulaeha Mabud; Bujur Jalali (International Journal Of Electrical Engineering and Inteligent Computing, 2023)
In terms of communication skills, many of us have limitations and shortcomings or what we are more familiar with is speech impairment Speaking is the ability to pronounce articulated sounds or words to express, express and convey thoughts, ideas and feelings. Communication skills can include many ways, including using verbal skills, namely verbally and non-verbally. In Indonesia, there are two sign languages used, namely Indonesian sign language (BISINDO) and Indonesian sign system (SIBI). BISINDO is a sign language that appears naturally in Indonesian culture and is practical for use in everyday life so that BISINDO has several variations in each region. The flex sensor has a thin and densely curved shape so that the flex sensor can be used as a motion detection and finger curve. Flex sensor application for human movement detection, patient monitoring. Therefore, hand-to-letter/text sign language translators using flexible sensors is a very important problem today. The method carried out is system design using tools and components used in research. This tool using the working principle in this system is to translate the sign language of alphabetic letters using flexible sensors. Design sign language translation of alphabetic letters using flexible sensors. The test to display the letters of the alphabet A-Z has a total minimum and maximum resistance at a flexible session of 1000 ohms with a voltage of 5V each. The result of this data is that there is no error in the play because the range value does not violate each other with other range values